Le carnaval des mots dans Les Fleurs bleues de Raymond Queneau - Laurichesse, Jean-Yves (Romanica Silesiana)
The aim of the article is to analyse the literary games in Raymond Queneau’s Les fleurs bleues (1965), where a double story is told: that of the duke of Auge and of Cidrolin, the two characters dreaming about each other. The narratives constitute a meditation on History and on human condition. The author plays with the ludic carnivalesque by employing “neo-French”. He plays both with the language, by modifying the ordinary usage, and with single words, which is even more creative. Furthermore, Queneau’s literary games include intertextuality and hypertextuality. Key words: Double-story, ludic, carnivalesque, inter- and hypertextuality.